Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

solve for x: log x+1 (x 2 + x - 6) 2 = 4 log 5 120 + (x - 3) – 2.log 5 (1 – 5 x-3 ) = -log 5 (0.2 – 5 x-4 )

solve for x:
  1. logx+1(x+ x - 6)= 4
  2. log5120 + (x - 3) – 2.log5(1 – 5x-3) = -log5(0.2 – 5x-4)

Grade:12

1 Answers

Harishwar IIT Roorkee
askIITians Faculty 50 Points
6 years ago
logx+1(x2+ x – 6)2= 4
It can be written as = (x2+ x – 6)2 = x+1 ^4
Solve this and find x

Also use
Log Rules:
1) logb(mn) = logb(m) + logb(n)
2) logb(m/n) = logb(m) – logb(n)
3) logb(mn) = n · logb(m)

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free

10th iCAT Scholarship Test Registration Form